FACTORS AFFECTING THE ECONOMIC VALUE OF AGRICULTURAL LAND TRANSFORMATION IN EAST JAVA PROVINCE - Gatot Ariya Dewanta; Mohammad Rondhi (UPT Penerbitan Universitas Jember, 2022)
The high rate of conversion of agricultural land is not balanced with the availability of agricultural land being cultivated. The area of ​​agricultural land is estimated to be around 5.1 million ha in 2045. This study discusses the effect of land value on the process of conversion of agricultural land that occurred in 31 sub-districts in East Java Province, Indonesia. The research method used in this study uses land cover spatial data analysis to see the distribution of land change in 31 areas that are processed using Qgis and multiple linear regression analysis to see the level of relationship between the independent and dependent variables of the study, namely land change, land value, productivity, income, and location. The results showed that during 2014 – 2018 in East Java Province there was a land change of 182.28 ha/year. The biggest changes occurred in urban areas as the basis of the regional economy. The relationship between land value variables has a positive effect on the conversion of agricultural land, which means that the greater the value of the land, the faster the process of conversion of agricultural land will be..